DGI-056 Reduced Delay in the Administration of Chemotherapy After Optimising the Process of Preparation/Dispensing of Parenteral Antineoplastics. (12th March 2013) - Borrell, C; Esteban, MJ; Ruiz, J; Megías, JE; López, E; Poveda, JL
Abstract : Background: Separation between the Chemotherapy Unit and the Day Hospital Unit makes rapid treatment of onco-hematologic patients difficult. Purpose: To optimise the sequence of dispensing parenteral antineoplastic mixtures when there is relevant physical separation between the Chemotherapy Unit (CU) of the Pharmacy Department and the Day Hospital Unit (DHU) where these treatments are administered to onco-hematologic patients. Materials and Methods: We reviewed stability data from mixtures of antineoplastics, each from Pharmacotherapeutic Schemes (PS) and updated the protocol in our Oncofarm programme. To plan the appointments of onco-haematological patients in the DHU, patients were grouped into three types depending on the stability of the mixtures and the total time of administration: type I [analysis (A), cheque (V) administration and chemotherapy (CT) on the same day], type II (A: one day, with V and CT the next day) and type III (A and V one day, with CT the next day). To evaluate the efficiency of the process, the compliance productivity indicator 'lag time' between confirming the treatments prescribed by doctors and the start of their administration in DHU was calculated. Results: With support from various literature sources, we reviewed the stability of 54 antineoplastic mixtures and updated the Oncofarm data. Of 482 PS analysed, 30% would be appropriate for type I patients, 2% for type II and 68% for type III. The new stability data allowed us to prepare a total of 28 new PS in the CU the day before their administration. To gauge productivity the 'lag time' was calculated for a period of three months for treatments prescribed electronically to 552 patients and the 1023 mixtures dispensed to DHU. The average delay was 2:23 (SD=0:37) hours, keeping the level of compliance at 100%. Conclusions: The reorganisation of the antineoplastic preparation process based on the updated stability data made it possible to dispense the mixtures of PS prescribed for type II and III patients at the best time. This ensured optimum services to health professionals and patient satisfaction. No conflict of interest.